2019
DOI: 10.1016/j.hpb.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Major intraoperative bleeding during pancreatoduodenectomy - preoperative biliary drainage is the only modifiable risk factor

Abstract: Most predictive parameters for major intraoperative bleeding are not modifiable. PBD is an independent predictor for major intraoperative bleeding and to reduce the risk, patients with resectable periampullary tumors should, if possible, be subject to surgery without preoperative biliary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…As shown previously 11 , national 30‐ and 90‐day mortality rates were low in comparison with contemporary cohorts from Germany, France and the USA, and in line with rates reported from Sweden and the Netherlands 1,2,26–28 . Rates of any major complication, CR POPF and PPH grade C were equal to coeval cohorts from the USA, Netherlands and Germany 22,29,30 . The relaparotomy rate in the present cohort (18·1 per cent) was similar to, or somewhat higher than, that reported from other studies 22,30,31 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As shown previously 11 , national 30‐ and 90‐day mortality rates were low in comparison with contemporary cohorts from Germany, France and the USA, and in line with rates reported from Sweden and the Netherlands 1,2,26–28 . Rates of any major complication, CR POPF and PPH grade C were equal to coeval cohorts from the USA, Netherlands and Germany 22,29,30 . The relaparotomy rate in the present cohort (18·1 per cent) was similar to, or somewhat higher than, that reported from other studies 22,30,31 .…”
Section: Discussionsupporting
confidence: 89%
“…The relaparotomy rate in the present cohort (18·1 per cent) was similar to, or somewhat higher than, that reported from other studies 22,30,31 . Compared with similar population‐based cohorts 29,30 , the median operating time of 322 min was short and median estimated blood loss (350 ml) was low.…”
Section: Discussionsupporting
confidence: 83%
“…The negative impact of IBL on outcomes after pancreatic surgery has long been suspected [ 29 34 ]; however, there have been few reports demonstrating risk factors for IBL [ 32 , 33 ]. Rystedt et al retrospectively analyzed 1864 patients who had undergone a PD in the Swedish National Pancreatic and Periampullary Cancer Registry.…”
Section: Discussionmentioning
confidence: 99%
“…Rystedt et al retrospectively analyzed 1864 patients who had undergone a PD in the Swedish National Pancreatic and Periampullary Cancer Registry. The national study on resectable periampullary tumors shows that the preoperative independent risk factors associated with major IBL (≥1000 mL) were male sex, body mass index ≥25 kg/m 2 , preoperative biliary drainage, C-reactive protein ≥12 mg/L, and neo-adjuvant chemotherapy treatment [ 32 ]. Seykora et al conducted a multi-institutional retrospective study and precisely evaluated 5323 PD patients who had been treated for either benign or malignant disease by 62 surgeons from 17 institutions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study based on SEER database in USA showed that the utilization of preoperative biliary stent placement doubled from 1992 to 2007 [2]. However, since the 21st century, with the continuous progress of surgical technology and perioperative management, more and more studies have shown that PBD could not bene t the patients, on the contrary, it can increase the postoperative complications [3][4][5][6][7][8][9]. But in clinical practice, there are still many situations that patients need PBD due to different reasons.…”
Section: Introductionmentioning
confidence: 99%